METASTATIC COLORECTAL TREATMENT COSTS OF USING TARGETED DRUGS IN SECOND AND FURTHER LINES THERAPY - N. A. Avxentyev; E. V. Derkach; E. A. Pyadushkina; M. D. Ter-Ovanesov (Фармакоэкономика, 2016)
Targeted drugs are recommended for treatment of metastatic colorectal cancer. Second and further lines therapy options include anti-EGFR therapy, eligible for patients with wild-type KRAS (cetuximab and panitumumab), and relatively new drug — regorafenib, which could be used for all patients.The aim of this study is to compare costs associated with these options in Russia.Materials and methods. We calculated cost of medication for treating one patient during one month with cetuximab, panitumumab and regorafenib. We also employed cost-effectiveness analysis, but its results should be treated with caution due to non-comparable patients in regorafenib and anti-EGRF drugs studies.Results. We found that monthly per patient medication costs of using regorafenib are 255,000 rubles, which is 104,000 rubles less when using cetuximab or 184,000 rubles less when using panitumumab. Cost-effectiveness ratio for regorafenib was estimated at 111,500 rubles per month and is the lowest among the alternatives: 136,000 rubles per month for cetuximab and 310,000 rubles per month for panitumumab.Conclusions. Regorafenib is cost-saving alternative for treatment of metastatic colorectal cancer in second and further lines therapy compared to cetuximab and panitumumab in Russia.